ZnO nanowire UV photodetector with multiple channels. Issue 1 (2nd January 2018) - Jiang, Guohua; Zhao, Dongmei; Zhao, Bo
Abstract : Purpose: The purpose of this paper is to investigate the optoelectronic properties of the multichannel ZnO UV photodetectors. Design/methodology/approach: ZnO nanowires were assembled by dielectrophoresis for the UV photodetectors. Different ZnO channels were adjusted by different alternating current voltages and investigated for UV optoelectronic properties. Findings: The number of the ZnO channels increases with the enhancing alternating current voltage. Optimum performance of the UV photodetectors is obtained with more channels. Originality/value: Dielectrophoresis is a promising method for controllable assembly of multichannel ZnO photodetectors. ZnO photodetectors with more channels demonstrate a good response to 380-nm UV light, which shows great potential application in UV photodetector.